Intra-ocular hydatid cyst in a child: A rare presentation. Issue 3 (May 2023) - Kumar, Vinod; Surve, Abhidnya; Biswal, Debasish; Verma, Nishant; Kashyap, Seema; Venkatesh, Pradeep; Mirdha, Bijay Ranjan
Intra-ocular cystic lesion in a young child can be parasitic lesion, old retinal detachment with cysts or simply a vitreous cyst. Intra-ocular localization of hydatid cysts is extremely rare accounting for less than one percent of all cases. This case describes a young child with left eye pain, redness and progressive diminution of vision with progressively enlarging intra- ocular cyst. Diagnosed as intra-ocular hydatid cyst, the radiological, intraoperative and microbiological features of same are described. Also, the management required in such a case is discussed.